EFFECTS ANALYSIS OF MEASURES OF WORKING CAPITAL MANAGEMENT ON FINANCIAL PERFORMANCE OF NON-FINANCIAL FIRMS LISTED IN NIGERIA (Journal of Global Accounting, 2023)
To make the most profitable use of every business’ scarce resources and for such organization to actualize the defined goal(s) of its existence, the place of working capital management (WCM) is considered paramount to its continuity and non-exposure to insolvency that often lead to its untimely cessation from business due to the mismanagement of the business’ Current Assets and Current Liabilities. Thus, this study analyzed the effect of various measures of working capital management on financial performance of non-financial firms listed on the Nigerian Exchange Group for the period, 2008-2022. The WCM measures used were average collection period and inventory conversion period. As a result, the ex-post facto research design was adopted, with secondary data obtained from annual reports of the sixteen (16) selected non-financial firms.  With the aid of Feasible generalized least squares (FGLS) regression analysis, the hypotheses were subjected to test and it was discovered that Average collection period had a significant effect on Return on Assets while Inventory conversion period had an insignificant effect on Return on Assets.  Also, Inventory conversion period and Average collection period had a significant effect on Return on Equity.  In conclusion, given the advancement of technology with its components of cashless policy, internet advertisement and trading, firms with a good rationing technique and dynamic credit policy that is consistent with reoccurring changes in the competitive domestic and international market can readily benefit from steady increase in Return on Assets and Return on Equity, regardless of the attendant increase in Average collection period and Inventory conversion period from time to time.  The study therefore recommends that firms should make the most use of technology and all its facets for business operations and growth purpose so as to adequately serve customers and also maintain adequate liquidity by maintaining  a strong customer base.
Keywords: Average collection period; Inventory Conversion period; Return on Assets; Return on Equity